ULTRASOUND-GUIDED PERIPHERAL VENIPUNCTURE: PREVALENCE OF SUCCESS AND ASSOCIATED FACTORS - Andrey Maciel de Oliveira; Mitzy Tannia Reichembach Danski; Edivane Pedrolo (Universidade Federal do Paraná, 2017)
The objective of this study was to analyze factors associated with a successful first attempt to ultrasound-guided peripheral venipuncture in adults. An analytical cross-sectional study was carried out in an emergency care unit in the South region of Brazil in April 2015. The participants were submitted to ultrasound-guided peripheral venipuncture. Ninety-seven participants were included. The prevalence ratio of success was 43% higher in visible veins and 128% higher in rectilinear veins. No significant association was found between the variables analyzed and the reduction of the prevalence of success at the first attempt. The presence of rectilinear and visible veins was the main factor associated with success at the first attempt.